2019
DOI: 10.1016/j.parkreldis.2019.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Retinal layers in Parkinson's disease: A meta-analysis of spectral-domain optical coherence tomography studies

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
78
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 68 publications
0
78
0
7
Order By: Relevance
“…On the other hand, one of the main strengths of this study is related to the short disease duration of PD patients. Considering that several studies showed that macular thinning correlates with PD severity (17,19,31,50), our finding of a reduced retinal thickness in early PD patients could suggest the use of this biomarker as a hallmark of brain degeneration. To support our hypothesis, future larger longitudinal studies on progression of retinal thickness along with microvascular abnormalities are surely needed, and it could be interesting to evaluate how fast the changes occur in retinal morphology as compared to in retinal vascularization, and vice versa.…”
Section: Discussionmentioning
confidence: 60%
“…On the other hand, one of the main strengths of this study is related to the short disease duration of PD patients. Considering that several studies showed that macular thinning correlates with PD severity (17,19,31,50), our finding of a reduced retinal thickness in early PD patients could suggest the use of this biomarker as a hallmark of brain degeneration. To support our hypothesis, future larger longitudinal studies on progression of retinal thickness along with microvascular abnormalities are surely needed, and it could be interesting to evaluate how fast the changes occur in retinal morphology as compared to in retinal vascularization, and vice versa.…”
Section: Discussionmentioning
confidence: 60%
“…To date, only one neuroimaging study has evaluated in vivo the relation between retinal thickness and the integrity of brain regions involved in motor manifestations of PD, finding an association between inner retinal atrophy and lower dopamine transporter uptake in substantia nigra 43 . However, the majority of previous OCT studies in PD failed to demonstrate statistically significant results or yielded contradictory findings regarding the link between retinal atrophy and motor disability or disease duration 22 . Given that macular GCIPL atrophy has been reported in de novo PD patients 23 and in prodromal phases of LBD 24 and the lack of its correlation with disease duration or motor manifestations, it may suggest that retinal injury is an early phenomenon of iPD.…”
Section: Discussionmentioning
confidence: 99%
“…Retinal neurodegeneration, neuronal loss, and anomalous α‐synuclein deposits within inner retinal layers are now well‐known pathological features of LBD patients 21 . Several cross‐sectional studies using OCT have demonstrated that, compared to age‐matched controls, PD patients have an atrophy of inner retina that seems to be associated with disease duration and motor disability 22 . More recent publications have shown that the thinning of macular GCIPL in PD is linked to cognitive impairment in de novo patients 23 and to the risk of dementia 18 .…”
mentioning
confidence: 99%
“…Among them, the retina has been recently proposed to reflect the PD brain pathology: phosphorylated α-synuclein deposits, similar to Lewy bodies, have been found in the retina of PD patients, whose density correlated with disease severity. 2,3 In addition, PD patients present several visual symptoms, such as reduced amplitudes in b-waves and oscillatory potentials on electroretinograms (ERGs), reduced visual evoked potentials, inner retinal layer thinning by optical coherence tomography (OCT), 4 impaired motion perception, contrast sensitivity, and color discrimination, [5][6][7][8] circadian rhythm dysfunction, 9,10 and melanopsin-containing retinal ganglion cell (mRGC) degeneration. 11 Considering the described similarities between the neurodegenerative process in the retina and brain, it is natural to wonder whether the dopaminergic cells in the retina are involved in the disease as they are in the brain.…”
Section: Introductionmentioning
confidence: 99%